DESIGN LEARNING ABOUT REFLECTION WITH PMRI APPROACH IN CLASS VII - Firdaus, Firdaus; Hartono, Yusuf; Somakim, Somakim (Sriwijaya University Learning and Education International Conference, 2018)
In the process of learning about reflection, some teachers teach the concept of reflection in an abstract way. As a result students have difficulty in understanding the concept transformation of reflection. This study aims to build students' understanding of the reverse context of